Answer:
(1, -3) is a solution to the system of equations ⇒ B
Explanation:
Let us solve the system of equations
∵ 3x + 2y = -3 ⇒ (1)
∵ 3x - y = 6 ⇒ (2)
→ Subtract equation (2) from equation (1)
∵ (3x - 3x) + (2y - -y) = (-3 - 6)
∴ (0) + (2y + y) = (-9)
∴ 3y = -9
→ Divide both sides by 3 to find y
∴ y = -3
→ Substitute the value of y in equation (2) to find x
∵ 3x - (-3) = 6
∴ 3x + 3 = 6
→ Subtract 3 from both sides
∵ 3x + 3 - 3 = 6 - 3
∴ 3x = 3
→ Divide both sides by 3 to find x
∴ x = 1
To check the answer substitute the values of x any in each equation if the two sides of the equation are equal, then the solution is right
∵ 3x + 2y = -3
∵ 3(1) + 2(-3) = -3
∴ 3 - 6 = -3
∴ -3 = -3
→ The two sides of the equation are equal
∵ 3x - y = 6
∵ 3(1) - (-3) = 6
∴ 3 + 3 = 6
∴ 6 = 6
→ The two sides of the equation are equal
∴ The solution satisfies the two equations
∴ (1, -3) is a solution to the system